History, women and gender in the modern Middle East - Pollard, Lisa, author.
1 online resource.
Keywords: "This introductory text explores the gendered history of the modern Middle East, from the eighteenth century to the present, studying the various ways in which gender has defined the region and shaped relations in the modern era. Richly illustrated and accessible for a variety of readers, History, Women and Gender in the Modern Middle East is an ideal resource for undergraduate and postgraduate students in gender studies and Middle Eastern history"--